HIGH SCHOOL STUDENTS’ LEARNING OBSTACLES IN UNDERSTANDING FRACTIONAL EXPONENTS AND ROOT FORMS (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2018)
Fractional exponents and root forms are one of the keys concepts in advanced mathematics courses; students’ dynamics in understanding these more complex mathematical processes consequently merits a thorough analysis. Nineteen high schools students were given a test with a series of fractional exponents and root forms related questions, with a varying degree of complexity. We then analyzed students’ answer and classified the underlying learning obstacles based on errors found in students’ answers. Several didactical and epistemological obstacles were found which indicates that learning design for these concepts needs to be improved.
Keywords: concept image; didactical and ephistimological; learning obstacle